Facing the Fiend Satan as a Literary Character. - Baillie, Eva Marta (Cambridge : The Lutterworth Press, 2014)
With the preponderance of visual imagery in our late modern period, why is it the literary Satan keeps emerging? And what can the literary figure of Satan contribute to the understanding of evil? Eva Marta Baillie argues that the literary is the only means by which Satan can survive, and that as a result of the changing literary (and cultural, philosophical, and theological) landscape and our changing perceptions of evil as we move into the twenty-first century, the satanic character must also change.
Front cover; Half title; Title page; Copyright; Contents; Acknowledgments; Abbreviations; Introduction: Setting the Stage; The Birth of a Character; Part One: The Dwelling Place of Satan; 1. Is Satan Evil?; 2. Satan's Biography; 3. Satan in Story and Myth; 4. Satan and the Written Word; Part Two: Satanic Characters; 5. The Restless Wanderer; 6. The Tormented Shadow; 7. The Zeroing Zero; 8. The Creative Eliminator; 9. The Stumbling Block; 10. The Transgressor; Conclusion: Satan's Salvation or the Redemption Lies in the Text; Bibliography; Back cover.
Print version record.
Includes bibliographical references.
Master record variable field(s) change: 072
Keywords: Devil -- History of doctrines; Devil in literature; Divination -- History; Devil -- History of doctrines; Devil in literature; Divination -- History; BIOGRAPHY & AUTOBIOGRAPHY -- Literary; Devil -- History of doctrines; Devil in literature; Divination; RELIGION / Christian Theology / Angelology & Demonology; Electronic books; History